ANALISIS ANALISIS PENGARUH VARIASI SLICE THICKNESS TERHADAP KUALITAS CITRA DAN INFORMASI ANATOMI PEMERIKSAAN MSCT SCAN THORAX PADA KASUS EMPHYSEMA DI RSD MANGUSADA BADUNG - nirma, Nirmala; Ni Putu Rita Jeniyanthi; Cokorda Istri Arywidiastuti (Lembaga Pengembangan Kinerja Dosen, 2023)
One of the clinical features that can be found in Thorax is emphysema. Emphysema is one of the pathological processes of the lung parenchyma in COPD (Chronic Obstructive Pulmonary Disease). The patient must inhale and exhale with a larger volume of air in order to meet the metabolic needs of oxygen distribution (O2), removal of carbon dioxide (CO2) and maintaining acid-base balance. MSCT has an important role in diagnosing emphysema. One of the biggest drivers for technical improvement in MSCT is image quality. MSCT Scan image quality is influenced by several factors, namely spatial resolution, resolution contrast, noise, and artifacts. One of the parameters that affect image quality is the selection of slice thickness. Slice thickness is the thickness of the slice or slice of the object being examined. Thorax MSCT scan is routinely performed using a slice thickness of 1.25 – 5 mm. Thorax examination in cases of emphysema used a slice thickness of 0.5 mm – 1.5 m.This type of research is quantitative with an experimental approach. This study was conducted by analyzing the effect of slice thickness variations on image quality and anatomical information of MSCT Scan Thorax in cases of Emphysema. Based on the results of the Friedman test overall, it shows that there is an influence of image quality and anatomical information on the MSCT Scan Thorax examination in cases of emphysema using slice thickness variations of 1.5mm, 3mm and 4.5mm on spatial resolution, contrast resolution, and noise. Based on the results of this study, the researcher can recommend the MSCT Scan Thorax examination in cases of emphysema using a slice thickness of 1.5mm with the aim that the results of image quality and anatomical information on the MSCT Scan Thorax examination in cases of emphysema look clear and good.